1999
DOI: 10.1046/j.1365-2818.1999.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

A procedure to prepare cultured cells in suspension for electron probe X‐ray microanalysis: application to scanning and transmission electron microscopy

Abstract: SummaryWe describe a simple procedure to prepare cultured cells in suspension to analyse elemental content at the cellular level by electron probe X-ray microanalysis. Cells cultured in suspension were deposited onto polycarbonate tissue, culture plate well inserts, centrifuged at low g, washed to remove the extracellular medium, cryo®xed and freeze-dried, and analysed in the scanning mode of a scanning electron microscope. We tested the effect of different washing solutions (150 mM ammonium acetate, 300 mM su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Preparation of whole cells for X‐ray microanalysis was described in detail elsewhere (Fernández‐Segura et al, 1999a). Briefly, cells were removed from the culture medium and transferred into polycarbonate tissue culture plate well inserts (Millicell‐PCF), which were transferred to conical centrifuge tubes and centrifuged at 170 g for 3–5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of whole cells for X‐ray microanalysis was described in detail elsewhere (Fernández‐Segura et al, 1999a). Briefly, cells were removed from the culture medium and transferred into polycarbonate tissue culture plate well inserts (Millicell‐PCF), which were transferred to conical centrifuge tubes and centrifuged at 170 g for 3–5 min.…”
Section: Methodsmentioning
confidence: 99%
“…27 Briefly, cells were removed from the culture medium and transferred into polycarbonate tissue culture plate well inserts (Millipore, Bedford, MA), which were in turn transferred to conical centrifuge tubes and centrifuged at 170×g for 3-5 min. After centrifugation, polycarbonate membrane filters were cut from their polystyrene holder and washed with ice-cold distilled water for 5 s to remove the culture medium.…”
Section: X-ray Microanalysismentioning
confidence: 99%
“…Marshall and Condron showed that the depth from which 90% of the emitted x‐rays from all elements in a FH sample were detected was approximately 2 μm and that the lateral resolution was also about 2 μm. Measurements of electron penetration in FD cultured cells (Fernandez–Segura et al ., 1999) have yielded similar estimates of depth resolution to those calculated here for FD retina, however, the estimate of depth resolution (17 μm) in FD retina at 15 kV contrasts markedly with a depth resolution of 0.5 μm at 10 kV suggested by Liang et al . (2004) and Crewther et al .…”
Section: Resultsmentioning
confidence: 99%